Genetic analysis of yield and quality attributes in fodder cowpea (Vigna unguiculata (L.) Walp) - Radhika V S (Department of Plant Breeding and Genetics, College of Agriculture, 2003)
An experiment on "Genetic analysis of yield and quality attributes in fodder cowpea [Vigna unguiculata (L.) Walp.]" was carried out at the Department of Plant Breeding anti Genetics, College of Agriculture, Vellayani during 1999-2002 with the objective of estimating combining ability heterosis and gene action. Fifty one diverse genotypes were evaluated for yield and quality attributes. Each genotype was replicated twice. The observations on plant height, number of primary branches per plant, number of leaves per plant, total , . leaf area, days to 50 per. cent flowering, days to maturity, leaf/stem ratio, leaf area index, dry weight of leaf, dry weight of stem, green fodder yield, dry matter yield, crude protein content, crude fibre content, calcium content and phosphorus content were recorded. Variability studies indicated high GCV and pev for dry weight of stem, dry matter yield and green fodder yield. High estimates of heritability (>70 per cent) were recorded for all the characters except number of primary branches per plant. High heritability and genetic advance were observed for dry weight of stem, dry weight of leaf, green fodder yield, dry matter yield, leaf area index and crude fibre content. Leaf/stem ratio, leaf area index, dry weight of stem, dry weight of leaf, plant height and number of primary branches per plant showed positive significant correlation with both green fodder yield and dry matter yield. A discriminant function was fitted with 12 variables to derive a selection index for 51 accessions based on their yield and yield attributes. The top ranking seven accessions, IFC 95102, IFC 8401, UP 9001, EC 4216, EC 240744, EC 241027 and HES 82 were selected as lines (female parents) for hybridization. Another discriminant function was fitted to derive a selection index to evaluate the quality parameters viz., crude protein content and crude fibre content. Three top